Preface and Constitution of the Asian Society of Ichthyologists - Page, Lawrence M.; Nor, Siti Azizah Mohd (Zootaxa, 2015)
The U.S. National Science Foundation-funded (DEB 1022720) ‘All Cypriniformes Species Inventory’ was initiated in 2010 and will be completed in 2015.  It has accelerated the rate of discovery and description of cypriniform fishes, expanded our knowledge of the phylogenetic relationships of cypriniforms, increased the capacity for systematic research in other countries through student training and establishing long-term collaborations, including conferences in Thailand in 2012, Brunei in 2013, Burundi in 2013, and Malaysia in 2014, led to the formation of the Asian Society of Ichthyologists, and made available large numbers of specimens and tissues of freshwater fishes, including many species never before collected, in permanent collections in foreign and U.S. institutions.